Multi-time-scale economic scheduling method for electro-hydrogen integrated energy system based on day-ahead long-time-scale and intra-day MPC hierarchical rolling optimization - Zhang, Leiqi; Dai, Wuzhen; Zhao, Bo; Zhang, Xuesong; Liu, Min; Wu, Qiliang; Chen, Jian (Frontiers in Energy Research, 2023)
To build a clean, secure, and efficient energy system, the hydrogen energy is an important developing trend for the energy revolution, and electro-hydrogen coupling system is expected to play an important role in the future. To obtain the optimal economic scheduling of the electro-hydrogen integrated energy system (E-H IES), this paper firstly establishes a refined model of the electrolyzer and hydrogen fuel cell (HFC), and then proposes an optimal scheduling model based on day-ahead long-time-scale optimization and intra-day model predictive control (MPC) hierarchical rolling optimization. In the day-ahead stage, a long-time-scale optimization considering the impact of multi-day forecast information is proposed when performing the day-ahead optimization to achieve the effect of inter-day energy transfer of hydrogen energy and improve the overall economic efficiency. In addition, during the intra-day stage, the MPC is adopted to implement hierarchical rolling optimization to track and correct the day-ahead schedule and achieve coordinated operation between multi-energy systems while taking into account the different energy transfer characteristics. Finally, the simulation results demonstrate the feasibility of the proposed optimal scheduling model and the effectiveness of the proposed multi-time scale economic scheduling method.